THE POWER OF SPEECH ACTS OF DEMONIC EXORCISM PRAYERS IN THE FILM POPE’S EXORCIST (2023 - Kevin Georgy Kilen; Diana Anggraeni; Bob Morison Sigalingging (Journal of Language and Literature, 2025)
This research analyzes the exorcism prayers uttered by the main character in the exorcism ritual scene in the film The Pope's Exorcist (2023). The purpose is to examine the elements of speech acts based on Austin's theory (1962) developed by Searle (1969). The elements include locutionary, illocutionary, and perlocutionary. The research also seeks to determine whether the exorcism prayers fall into the constative or performative category. The research employs a descriptive qualitative method using a pragmatic analysis approach. The results show 5 data on each element of speech acts that are interrelated. In the locutionary act, the 5 data contain literal meanings in accordance with the three main aspects, namely phonetic, phatic, and retic. Illocutionary act consists of 3 expressive and 2 directives. While perlocutionary act include 3 that cause surprising, 1 dissuading, and 1 persuading. In terms of speech categories, 2 are constative and 3 are performative. This research contributes to pragmatic linguistic analysis in religious-horror films and offers insights into language use in Chatolic Church ritual practices, particularly exorcism.